Decomposing the Increase in TIMSS Scores in Ghana : 2003–2007 - Sakellariou, Chris (World Bank, Washington, DC, 2012)
This paper attempts to explore certain aspects underlying the substantial improvement in 8th grade student performance in Ghana on the Trends in International Mathematics and Science Study from 2003 to 2007.